Management of Typhoid Fever in Children: A Literature Review - Sayyidusy, Assagaf; Sam'aarif, Sam'aarif; Kartika, Dewi; Wafanjar, Wafanjar; Aprianti, Nurul; Sarmila, Sarmila; Veronika, Maria; Indah, Suci; Purnamasari, Anisa (PT. Nursing Genius Care, 2025)
Background: Typhoid fever is an infectious disease caused by the bacterium Salmonella enterica serotype Typhi (S. Typhi). It is one of the most common causes of fever, often presenting without distinctive features or specific signs of illness, particularly in areas with limited water sanitation and medical facilities. Purpose: To explore the management of typhoid fever in children. Methods: A systematic literature search was conducted using several databases, including ScienceDirect and Google Scholar. Boolean terms and search restrictions were applied to identify articles that appropriately addressed the research question. Inclusion criteria included full-text articles published between 2022 to 2025. Results: The search yielded 10 articles that met the predefined criteria and keywords. Conclusion: Active involvement of parents plays a crucial role in the management of typhoid fever in children. This role includes supervising treatment adherence, recognizing clinical symptoms, and understanding the importance of completing antibiotic therapy as prescribed by medical professionals.